Identify the Major Factors Driving to Agricultural Diversification in Telangana: The Impact of Economic Factors on Agricultural Diversification in Telangana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Examples of crop diversification of current agricultural technology, particularly amid the time of the Green Revolution in the late sixties and mid-seventies, there is a constant flood for expanded agribusiness as far as crops, essentially on economic contemplations. Indian horticulture is progressively getting impacted increasingly more by economic factors. This need not be astounding in light of the fact that water system extension, infrastructure development, infiltration of country markets, development and spread of brief span and dry season safe crop innovations have all added to limiting the role of non-economic factors in crop decision of even little ranchers. Liberalization and globalization strategies are going to reinforce the role of cost related economic motivations in deciding crop composition at both the small scale and large-scale levels. This paper has surveyed the diversification situation of horticulture at the national dimension and its appearance at homestead level of circumstance close by. It has been see that concentration proportion (CR4) for four major agricultural sub-areas has declined from 73.6 percent to 69.6 percent for the examination period, 1999-00 to2013-14. It plainly shows a move in Indian farming from oats based production example to other high-esteem based production design.